2019
DOI: 10.3390/rs11202452
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Urbanization and Climate on Vegetation Coverage in the Beijing–Tianjin–Hebei Region of China

Abstract: Worldwide urbanization leads to ecological changes around urban areas. However, few studies have quantitatively investigated the impacts of urbanization on vegetation coverage so far. As an important indicator measuring regional environment change, fractional vegetation cover (FVC) is widely used to analyze changes in vegetation in urban areas. In this study, on the basis of a partial derivative model, we quantified the effect of temperature, precipitation, radiation, and urbanization represented as nighttime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…Most of the studies focused on the impact of urbanization on urban precipitation and the impact of forest or farmland on regional precipitation, while there were few studies on the underlying surface structure and the change of regional water resources in the water-air cycle [17][18][19]. It was found that the change of urban construction land has an important influence on the change of regional precipitation, vegetation, and land surface temperature, but it failed to quantitatively express the influence among them [20][21][22]. By analyzing long-term precipitation data, Zhang et al found that the rapid expansion of urban land in Beijing since 1981 was statistically correlated with the decrease of summer precipitation in the northeast of Beijing from 1981 to 2005, and that the rise of surface temperature and the decrease of evaporation caused by urban expansion were the possible reasons for the change of summer rainfall [23].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies focused on the impact of urbanization on urban precipitation and the impact of forest or farmland on regional precipitation, while there were few studies on the underlying surface structure and the change of regional water resources in the water-air cycle [17][18][19]. It was found that the change of urban construction land has an important influence on the change of regional precipitation, vegetation, and land surface temperature, but it failed to quantitatively express the influence among them [20][21][22]. By analyzing long-term precipitation data, Zhang et al found that the rapid expansion of urban land in Beijing since 1981 was statistically correlated with the decrease of summer precipitation in the northeast of Beijing from 1981 to 2005, and that the rise of surface temperature and the decrease of evaporation caused by urban expansion were the possible reasons for the change of summer rainfall [23].…”
Section: Introductionmentioning
confidence: 99%
“…The invariant target area method specifically includes mutual correction, saturation correction, and continuity correction between images. This method has been widely used [81][82][83][84] and is considered to have high reliability. First, perform mutual correction of time series images.…”
Section: Extraction Of the Urban Built-up Areamentioning
confidence: 99%
“…Temperature and precipitation are two climate factors related to the geographical distribution of vegetation, which are important to the NPP in a dryland ecosystem (Wang et al 2019). Among all climate factors, precipitation has the greatest influence on the vegetation cover changes (Zhou et al 2019), is further related to the crop yield in the Hebei region (Wang et al 2020). In this study, we mapped the spatial correlation between temperature, precipitation and HANPP at pixel level based on the meteorological raster data.…”
Section: Correlation Between Climate Factors and The Hanppmentioning
confidence: 99%